The Combination of Coagulant and Electrocoagulation in Stabilized Leachate Treatment - Mohd Zin, Nur Shaylinda (International Journal of Sustainable Construction Engineering and Technology, 2024)
The contaminated leachate production is a result of solid waste disposal that has led to a negative impact on water and the environment. Therefore, leachate treatment is necessary to solve the problem. This study was conducted to determine the removal of color, suspended solids, chemical oxygen demand (COD), turbidity and ammonia nitrogen (NH3-N) for one-stage coagulation (chemical coagulation (alum)) under the influence of pH and dosage of alum, and also for two stages coagulation (chemical coagulation (alum) and electrocoagulation) under the effect of current density and the duration of current flow. The two-stage coagulation’s performance in this experiment was compared with one-stage coagulation. Chemical coagulation was conducted by using a jar test to identify the optimum of pH and the alum’s dosage. The results of this study revealed that the optimum dosage and pH for alum were 3 g/L and pH 6, respectively. The percentage removal of turbidity, color, suspended solids, COD and NH3-N by 3 g/L alum at pH 6 was 89.16%, 87.5%, 97.3%, 49.86% and 17.32%, respectively. Two stages of coagulation were conducted by using a combination of iron electrode plates (7 cm × 5 cm × 0.1 cm) and chemical coagulant (alum) in an electrolytic cell to determine the optimum current density and the duration of current flow. The result showed that the optimum current density and duration of current flow in the two stages of coagulation were 42.86 A/m² and 30 minutes, respectively. The percentage removal of the turbidity, color, suspended solids, COD and NH3-N by using the combination of 3 g/L alum at pH 6 and 42.86 A/m² of current density at 30 minutes duration of current flow was 93.39%, 89.47%, 96.58%, 78.05% and 44.25%, respectively. The combination of two stages enhanced the removal efficiency of coagulation especially for COD and NH3-N compared to one-stage coagulation. Thus, the two-stage coagulation method has the potential to be used in the leachate treatment.